Efficient electrochemical water oxidation to hydrogen peroxide over intrinsic carbon defect-rich carbon nanofibers. Issue 42 (21st October 2021) - Sun, Yanhui; Chen, Xin; Ning, Shangbo; Zhou, Wei; Yang, Zhongshan; Cui, Jiwei; Wang, Defa; Ye, Jinhua; Liu, Lequan
Abstract : Carbon nanofibers enriched in ring-defects significantly promote electrochemical water oxidation to hydrogen peroxide. Abstract : The two-electron water oxidation reaction (2e − -WOR) provides a promising route to produce hydrogen peroxide (H2 O2 ) from water; but it is currently hampered by low H2 O2 partial current. Here, intrinsic carbon defect-rich carbon nanofibers are demonstrated to be highly effective for electrochemical 2e − -water oxidation. A H2 O2 current density of 72.6 mA cm −2 is achieved at 2.9 V vs. RHE which is among the highest values reported for the 2e − -WOR. XPS and NEXAFS studies indicate that pentagonal and octagonal ring defects are dominant in the optimal sample. A combination of DFT calculations and a methanol competitive oxidation experiment reveals that ring defects effectively reduce the adsorption strength of OH*, which ultimately promotes the 2e − -WOR for valuable H2 O2 production. Our study makes a helpful attempt in exploring carbon-based materials for efficient 2e − -WOR electrocatalysts.